(untitled) (REMUNOM, 2024)
Agricultural gypsum, also known as soil conditioner, improves the physical, physical-chemical properties and biological activity of the soil. Its use in livestock farming will provide better nutrition for cattle, since the nutritional value of the forage plant will be enhanced through soil nutrition. Gypsum provides calcium and sulfur to the soil, improving its structure and allowing the grass to develop deeper roots. As a result, the plants will be more resistant to dry spells and will take longer to dry during drought, benefiting the rural producer.